ANALYSIS OF ELECTRONIC BANKING ( E-BANKING) USERS IN INDONESIA DURING AND AFTER THE COVID-19 PANDEMIC - Prastiwi, Putri Intan; Hanifah, Umi (LPPM Universitas Duta Bangsa Surakarta, 2023)
The purpose of this study is to examine the differences in the impact of the covid-19 pandemic on electronic banking users. This study used the Wixolcon Test analysis method to test the differences between paired data. Testing comparisons between observations before and after being given treatment and knowing the effectiveness of a treatment. The dependent variables in this research are mobile banking, internet banking and the dependent variable is the covid-19 pandemic. This research uses a quantitative research approach. The data source is from the official website of the Indonesian Stock Exchange, namely www.idx.co.id in 2019 - 2022. The total research population was 47 companies. The sampling method was purposive sampling so that a total sample of 39 companies was obtained. The results of the Wixolcon test, namely on the mobile banking variable, show that there are differences in mobile banking users in Indonesia during and after the Covid-19 pandemic. Regarding the internet banking variable, the results of internet banking research show that there are differences in internet banking users in Indonesia during and after the Covid-19 pandemic.